Photoperiod and Testosterone Modulate Growth and Melanogenesis of S91 Murine Melanoma - Allil, Paulo A. A.; Visconti, Maria A.; Castrucci, Ana Maria L.; Isoldi, Mauro C. (Medicinal Chemistry, 2008)
In vivo and in vitro assays were performed with S91 murine melanoma cells aiming to investigate the effects of testosterone and photoperiod on tumor growth and melanogenesis (tyrosinase activity). In vivo assays were performed by inducing melanoma tumors in castrated mice receiving increasing concentrations of testosterone and submitted to varying photoperiod regimens. The results demonstrated that the increase of melanin content was higher in animals submitted to the longest days, thus demonstrating the importance of photoperiod length in melanin synthesis. Increase in tumor growth and protein content was observed in testosterone-treated animals submitted to 12L:12D; in testosterone-treated animals submitted to 4L:20D and 20L:4D tumor growth was significantly smaller. In S91 cultured cells, testosterone increased cell proliferation and reduced tyrosinase activity in a dose-dependent manner. Radioactive binding assays demonstrated that the hormone was acting through low affinity testosterone receptors, since the presence of aromatase inhibitor did not affect the binding assay in a statistically significant way, and all the in vitro experiments were performed in the presence of the inhibitor. Our in vivo data added to the in vitro results corroborate the hypothesis that S91 melanoma cells directly respond to testosterone and that this effect is modulated by light.
Keywords: DBA/2J mice